Transcriptome Analysis Identifies Candidate Genes and Signaling Pathways Associated With Feed Efficiency in Xiayan Chicken - Xiao, Cong; Deng, Jixian; Zeng, Linghu; Sun, Tiantian; Yang, Zhuliang; Yang, Xiurong (Frontiers in Genetics, 2021)
Feed efficiency (FE) is a very important economic trait in poultry production, while the rate of feed efficiency is generally evaluated by residual feed intake (RFI). The molecular regulating mechanisms of RFI is unknown until now. Therefore, the objective of the current study is to identify candidate genes and signaling pathways related to FE employing RNA-seq in low residual feed intake (LRFI) and high residual feed intake (HRFI) in Xiayan chicken, a native chicken in Guangxi province. Chickens were divided into four groups based on FE and gender, namely LRFI and HRFI for males and females, respectively. The results showed we identified a total of 1015 and 742 differentially expressed genes (DEGs) associated with RFI in males and females, respectively. The 32 and 7 significant enrichment differential terms of Gene Ontology (GO) in the male and female chiefly involve carbohydrate metabolism, amino acid metabolism, and energy metabolism. Additionally, the Kyoto Encyclopedia of Genes and Genomes (KEGG) identified 11 and 5 significant enrichment signaling pathways, including nutrient metabolism, insulin signaling pathway, and MAPK signaling pathway, etc. Protein-protein interaction (PPI) network analysis illustrated that CAT, ACSL1, ECI2, ABCD2, ACOX1, PCK1, HSPA2, and HSP90AA1 might have an inevitable effect on feed efficiency, and these genes are mainly involved in the biological processes of fat metabolism and heat stress. Gene Set Enrichment Analysis (GSEA) indicated that the increased expression of genes in LRFI chickens was related to intestinal microvilli structure and function and the fat mental process in males. As for the female, the highly expressed set of genes in the LRFI group were primarily associated with nervous system development and cell development. Our finding has further improved the insights into RFI's regulation mechanism from the local chicken's perspective.